An evaluation of four private animal health and welfare standards and associated quality assurance programmes for dairy cow production. (December 2021) - More, S.J.; Marchewka, J.; Hanlon, A.; Balzani, A.; Boyle, L.
Highlights: Private QA programmes have the potential to substantially improve farm animal health and welfare. Only some of the QA programmes evaluated presented objective information to support claims. There were notable examples of best-practice in animal health and welfare. There is a need for greater scrutiny of private standards and QA programmes. Regulatory oversight may be needed, to build confidence among consumers of programme claims. Abstract: Private standards in animal health and welfare (AHW) and associated quality assurance (QA) programmes are an important instrument for food policy with the potential to substantially improve AHW. However, there are concerns that they do not necessarily do so. In this study, we evaluated four private AHW standards and associated QA programmes for dairy cow production, from Denmark, Ireland, the Netherlands and the United Kingdom, using an existing (but adapted) conceptual framework. The framework considers criteria relating to programme goals including relevance to AHW, programme beneficiaries, effectiveness, efficiency and transparency. The current study focused on information that was publicly available online. We found limited objective information to support programme claims, although there were considerable differences between programmes. Across all programmes, problems were identified with respect to transparency, and attempts to scrutinise claims would not be a straightforward process for most consumers. Among the programmes, there were notable examples of best-practice in AHW, relating to science-based evidence, separation of risk assessment and risk management, animal-based measures, farm benchmarking, ongoing programme-level metrics and measurement, and ongoing programme review. There is a need for careful scrutiny of private standards and QA programmes, to provide consumers with assurance with respect to programme effectiveness and transparency. Further, it is important that programme efficiencies are maximised. There is a strong case for regulatory oversight of private standards in AHW and associated QA programmes. This could be within existing or defined policy instruments, both to facilitate the positive impact of these programmes and to build confidence among consumers of the validity of programme claims.